حيثيات الحكم في المسألة الزنبورية بين سيبويه والكسائي: دراسة نقدية: Of the Zamburic Question: A Critical Study of the verdic between Sībawayh and Al-Kisā’ī - Bello, AbdulGaniyy Folonsho; Bin Abdullah, Mohd Ikhwan (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث كانت المسألة الزنبورية حادثة تاريخية خالدة، وهي عبارة عن مناظرة علمية وقعت بين الأسطورتين؛ سيبويه والكسائي. دارت هذه المناظرة حول جملة نصها: " كنت أظن أن العقربَ أشد لسعة من الزنبور فإذا هو هي أم فإذا هو إياها؟" كانت المناظرة شرسة، وقد أظهر كل منهما براعته ومهارته، وحيث حُسم الأمر فعلا لصالح الكسائي في نصب الحال، وحكم ضد سيبويه، فاندلعت ضجة كبرى وقامت لها القيامة ولم تقعد. وكان هذا هو الاعتقاد السائد، والانطباعات الموروثة من جيل إلى جيل، غير أن هذه الانطباعات تبنى على العواطف غير المنطقية ودون النظر إلى ظروف وحيثيات محتملة لسقوط سيبويه. تهدف هذه الدراسة إلى دراسة المسألة الزنبورية وحيثيات الحكم فيها، وأهم العوامل التي أدت إلى سقوط سيبويه وفوز الكسائي. وتستكشف الأسس المنهجية التي اعتمدها كل من سيبويه والكسائي في دراساتهم النحوية، وكيف ساهمت هذه الأسس في تشكيل منظومتهم النحوية. تعتمد هذه الدراسة على ثلاثة مناهج بحثية متكاملة؛ المنهج التاريخي لفهم التطور الزمني للنحو العربي والمنهج المقارن لمقارنة الآراء والتحليلات النحوية بين الأسطورتين، وكذلك المنهج النقدي لتقييم الآراء والنظريات النحوية المتباينة، وتفكيك بعض الانطباعات الموروثة عن هذه المسألة. تتوصل الدراسة إلى أنه من التحيز الظاهر والمحسوبية الجاهلية أن نبني الحكم على العواطف بأن الكسائي خدع سيبويه ليتغلب عليه، بل كانت مناظرة علمية وقضية منهجية. وفي الحين كان البصريون يعتمدون على القياس متشددين، كان الكوفيون يعتمدون على القياس والسماع، وكان المذهب الكوفي أكثر تشعباً وأوسع رواية، والمذهب البصري أوسع قياساً وأضيق رواية. ABSTRACT The zamburic question was an historical incident, a debate between the two legends; Sibawayh and Al-Kisa’i. This debate revolved around a sentence that reads: " Kuntu aẓun anna alʻqrba ashadd lasʻatan min al-Zanbūr fa ʼidhā huwa hiyyāā Ao faʼdhā huwa iyyāhā?" The debate was fierce, and each of them showed his skill and prowess, and when the matter was decided in favour of Al-Kisa’i and against Sibawayh, noises erupted among their followers. The allegation that Kisai set up Sibawahi in order to precail him was just a mere impression built on illogical emotions and without considering the possible circumstances and conditions for Sibawayh’s downfall. This study aims to study the zamburic question and the conditions for the ruling therein, and the most important factors that led to Sibawayh’s downfall and Al-Kisa’i’s victory. It explores the methodological foundations that both Sibawayh and Al-Kisa’i adopted in their grammatical studies, and how these foundations contributed to shaping their grammatical system. This study is based on three integrated research methods; the historical method to understand the chronological development of Arabic grammar, the comparative method to compare grammatical opinions and analyses between the two legends, as well as the critical method to evaluate the different grammatical opinions and theories, and to debunk some inherited impressions about this issue. The study concludes that it is an empty statement and, perhaps an act favoritism to accuse that Al-Kisa’i deceived Sibawayh to overcome him, but rather a deserved victory based on critical and metholodical examination of the debate and the circumstances sounding Sibawayh.